Day 2 Wed, February 01, 2023 2023
DOI: 10.2118/212342-ms
|View full text |Cite
|
Sign up to set email alerts
|

Overflush and Fracturing: Playing Poker with your Completion

Abstract: Since the inception of hydraulic fracturing, the industry has wrestled with the concept of over/under- flushing, and has always pitched this as a binary philosophy, attempting to determine/define that this is either a fundamentally good or a bad approach. This schism simply grew with the extensive development of unconventionals; the use of overflush being an inherent and fundamental requirement for an effective and economic unconventional completion sequence. This paper will demonstrate that the true answer, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Prior articles have noted the substantial care team resources required to address the growing volume of patient portal messages. 7 , 8 Our findings highlight potential disparities in how those resources are allocated across patient groups. Understanding and addressing these disparities will be necessary for improving care equity and informing algorithms.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Prior articles have noted the substantial care team resources required to address the growing volume of patient portal messages. 7 , 8 Our findings highlight potential disparities in how those resources are allocated across patient groups. Understanding and addressing these disparities will be necessary for improving care equity and informing algorithms.…”
Section: Discussionmentioning
confidence: 83%
“…Since the start of the pandemic, secure portal messages have become an increasingly important channel for patient–care team interaction. 5 , 7 Use of text-based health care communications is likely to continue to grow, evidenced by both traditional health care institutions, such as BMC, and the growing sector of digital-first care institutions, such as Firefly and Ginger, which often rely on text-based messaging with a health coach as a first-line triage point before patients receive clinician-based care. 22 Additionally, while AI tools have been discussed as a means for triaging and responding to patient text-based requests, 15 , 16 , 23 , 24 , 25 prior work has shown that AI tools can perpetuate underlying inequalities in the data that algorithms were trained on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation